Performance of an RT-nested PCR ELISA for detection of Newcastle disease virus - Kho, C.L; Mohd-Azmi, M.L; Arshad, S.S; Yusoff, K (Elsevier, 2000)
A sensitive and specific RT-nested PCR coupled with an ELISA detection system for detecting Newcastle disease virus is described. Two nested pairs of primer which were highly specific to all the three different pathotypes of NDV were designed from the consensus fusion gene sequence. No cross-reactions with other avian infectious agents such as infectious bronchitis virus, infectious bursal disease virus, influenza virus, and fowl pox virus were observed. Based on agarose electrophoresis detection, the RT-nested PCR was about 100 times more sensitive compared to that of a non-nested RT-PCR. To facilitate the detection of the PCR product, an ELISA detection method was then developed to detect the amplified PCR products and it was shown to be ten times more sensitive than gel electrophoresis. The efficacy of the nested PCR-ELISA was also compared with the conventional NDV detection method (HA test) and non-nested RT-PCR by testing against a total of 35 tissue specimens collected from ND-symptomatic chickens. The RT-nested PCR ELISA found NDV positive in 21 (60%) tissue specimens, while only eight (22.9%) and two (5.7%) out of 35 tissue specimens were tested NDV positive by both the non-nested RT-PCR and conventional HA test, respectively. Due to its high sensitivity for the detection of NDV from tissue specimens, this PCR-ELISA based diagnostic test may be useful for screening large number of samples.